The Indonesian Legal Framework to Mitigate Marine Plastic Debris - Chomariyah, Chomariyah; Rafiqi, Ilham Dwi (Universitas Muhammadiyah Malang, 2024)
This study aims to analyse and identify the problem of plastic marine debris in Indonesia and in the ASEAN Frame. This research employed a normative approach involving the implementation of the ASEAN Framework, Law No. 32 of 2009 concerning Environmental Protection and management, based on the principle of sustainability. The government and the local Government's duties are to ensure that marine debris will be implemented in a good manner and based on environmentally sound management, as in line with Presidential Regulation No. 83 Year 2018 on Marine Debris Management. This study also uses qualitative methods to explain and analyze the phenomena and social dynamics of marine plastic debris. The ASEAN framework involves the encouragement of the preparation of regional action plans to combat marine plastic debris. This is important, considering that the four ASEAN countries (Indonesia, Vietnam, Thailand, and the Philippines) are the largest producers of marine plastic debris in the world, while Indonesia is involved in every stage of environmental diplomacy in ASEAN. The research results show that the measures taken by ASEAN range from the initiation stage to the implementation of the ASEAN Regional Action Plan to Combat Marine Debris in ASEAN Member States 2021 – 2025 including in Indonesia. Every state performs its own marine debris management, depending on the Area, population, mastery of technology and state budget. Abstrak Penelitian ini bertujuan untuk menganalisis dan mengidentifikasi permasalahan sampah plastik di laut di Indonesia dan dalam kerangka ASEAN. Metode penelitian yang digunakan adalah pendekatan normatif, peraturan perundang-undangan dengan mengimplementasikan Kerangka ASEAN, Undang-Undang Republik Indonesia No. 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup, berdasarkan prinsip keberlanjutan. Tugas Pemerintah dan Pemerintah Daerah adalah menjamin pengelolaan sampah laut dilaksanakan dengan baik dan berdasarkan pengelolaan yang berwawasan lingkungan, Peraturan Presiden Nomor 83 Tahun 2018 tentang Pengelolaan Sampah Laut. Penelitian ini juga menggunakan metode kualitatif untuk menjelaskan dan menganalisis fenomena, dinamika sosial sampah plastik di laut. Kerangka kerja ASEAN adalah dengan mendorong penyusunan rencana aksi regional untuk memerangi sampah plastik di laut. Hal ini penting karena keempat negara ASEAN (Indonesia, Vietnam, Thailand, Filipina) merupakan penghasil sampah plastik laut terbesar di dunia. Indonesia terlibat dalam setiap tahapan diplomasi lingkungan hidup di ASEAN. Hasil penelitian menunjukkan, Di ASEAN mulai dari tahap inisiasi hingga implementasi Rencana Aksi Regional ASEAN untuk Memerangi Sampah Laut di Negara Anggota ASEAN 2021 – 2025 termasuk di Indonesia. Dalam melaksanakan pengelolaan sampah laut tidak selalu sama di setiap Negara, terdapat empat unsur yang membedakannya tergantung pada Luas Wilayah, jumlah penduduk, penguasaan teknologi dan anggaran pendapatan Negara.